2015
DOI: 10.1515/tjj-2014-0019
|View full text |Cite
|
Sign up to set email alerts
|

Gas Turbine Fault Diagnosis Using Probabilistic Neural Networks

Abstract: Efficiency of gas turbine monitoring systems pri marily depends on the accuracy of employed algorithms, in particular, pattern classification techniques for diag nosing gas path faults. In recent investigations many tech niques have been applied to classify gas path faults, but recommendations for selecting the best technique for real monitoring systems are still insufficient and often con tradictory. In our previous work, three classification tech niques were compared under different conditions of gas turbine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 14 publications
(35 reference statements)
0
20
0
Order By: Relevance
“…The results revealed that the proposed scheme was capable of diagnosing all the considered fault scenarios with sufficiently high accuracy. Recently, the fault classification performance of PNN was compared with MLP and RBF by Loboda and Robles [153], and obtained similar accuracies. In general, as per this review, most of the previous PNN based GT diagnostic techniques were utilized for fault classification tasks.…”
Section: Probabilistic Neural Networkmentioning
confidence: 90%
“…The results revealed that the proposed scheme was capable of diagnosing all the considered fault scenarios with sufficiently high accuracy. Recently, the fault classification performance of PNN was compared with MLP and RBF by Loboda and Robles [153], and obtained similar accuracies. In general, as per this review, most of the previous PNN based GT diagnostic techniques were utilized for fault classification tasks.…”
Section: Probabilistic Neural Networkmentioning
confidence: 90%
“…A PNN is a kind of neural network based on statistical principles, which is commonly employed to solve problems of pattern classification [30]. The PNN is an efficient and robust classifier, obtained when the Bayes strategy for decision making is combined with a non-parametric estimator for probability density functions [31].…”
Section: Probabilistic Neural Network (Pnn)mentioning
confidence: 99%
“…The task of the pattern layer is to calculate the pattern, matching the relationship between the testing samples and the training samples, and to centralize the categories with high similarity. The number of neurons in the pattern layer is equal to the sum of the number of trained samples in all categories, and the neuron X ij computes the pattern layer output as follows [30]:…”
Section: Probabilistic Neural Network (Pnn)mentioning
confidence: 99%
See 1 more Smart Citation
“…The components of monitoring and detection include data extraction, fault detection, fault location and prognosis [1][2][3][4]. Much of the current literature focuses on fault location algorithms which can be broken down into pattern recognition methods such as fuzzy logic [5,6], genetic algorithms [7], Bayesian belief networks [8][9][10], and neural networks [11][12][13][14] and model identification methods such as Kalman filtering [15] and weighted least squares [16][17][18]. But despite continuous developments in all of these physical and computational techniques, serious gas turbine problems can still quickly develop before corrective actions can take place.…”
Section: Introductionmentioning
confidence: 99%